Evaluation of clinical-demographic characteristics and cardiovascular risk–related comorbidities in patients with early-stage mycosis fungoides - Pelin Ertop Doğan; Aleyna Demirel; Pelin Aladağ; Emel Hazinedar (Medical Journal of Western Black Sea, 2026)
Aim: Mycosis fungoides (MF) is the most common type of cutaneous T-cell lymphoma and usually follows a chronic, indolent course. Chronic inflammation involved in MF pathogenesis may contribute to the development of cardiovascular and metabolic comorbidities. This study aimed to evaluate the clinical and demographic characteristics and cardiovascular risk–related comorbidities in patients with early-stage MF.Material and Methods: This retrospective study included 62 patients diagnosed with early-stage MF (stages 1A, 1B, and 2A according to the ISCL/EORTC classification) and followed between 2020 and 2024. Clinical and demographic data were analyzed. Metabolic and laboratory parameters were evaluated in a subgroup of 25 patients with complete data and compared with an age- and sex-matched control group of 25 individuals.Results: Among the patients, 59.7% were male. The median age was 53.5 years, and the median age at diagnosis was 51 years. According to disease stage, 48.4% of patients were classified as stage 1A, 35.5% as stage 1B, and 16.1% as stage 2A. The most common comorbidities were hypertension (46.8%), diabetes mellitus (33.9%), dyslipidemia (32.3%), and coronary artery disease (25.8%).In the subgroup analysis, median fasting blood glucose levels were significantly higher in the MF group compared with controls (107 mg/dL vs. 98 mg/dL; p = 0.009). No significant differences were observed between the groups regarding body mass index or lipid parameters.Conclusion: Cardiovascular risk–related comorbidities are frequent in patients with early-stage MF. Elevated fasting blood glucose levels, despite similar diabetes prevalence, may indicate early metabolic dysregulation. Careful metabolic monitoring of this patient population may therefore be warranted.